2022
DOI: 10.1101/2022.11.25.517950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wikipedia as a tool for contemporary history of science: A case study on CRISPR

Abstract: Rapid developments and methodological divides hinder the study of how scientific knowledge accumulates, consolidates and transfers to the public sphere. Our work proposes using Wikipedia, the online encyclopedia, as a historiographical source regarding contemporary science. We chose the high-profile field of gene editing as our test case, performing a historical analysis of the English-language Wikipedia articles on CRISPR. Using a mixed method approach, we qualitatively and quantitatively analyzed its text, s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Therefore, we hypothesized that tracking article creation can reflect the growing body of knowledge related to climate change that had accumulated between 2001 (Wikipedia's creation) and 2022. To follow these dynamics, we used the data supplied by the "corpus builder" (9,28) to create a timeline of corpus articles based on each of their Date Of Birth (DOB), (Fig 1D and Table S1). We found that as the corpus' size (i.e.…”
Section: Corpus Historical Dynamicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we hypothesized that tracking article creation can reflect the growing body of knowledge related to climate change that had accumulated between 2001 (Wikipedia's creation) and 2022. To follow these dynamics, we used the data supplied by the "corpus builder" (9,28) to create a timeline of corpus articles based on each of their Date Of Birth (DOB), (Fig 1D and Table S1). We found that as the corpus' size (i.e.…”
Section: Corpus Historical Dynamicsmentioning
confidence: 99%
“…They were however indicative of wider changes taking place in the table of content. Sections and their growth have previously been used by us (9) and others to map the growth of knowledge (37) on other scientific articles on Wikipedia. Alongside textual changes reflected in the article's text and size, we also observed changes in its TOC, which expanded and contracted over time (Fig 2C and Table S4).…”
Section: Structural Changesmentioning
confidence: 99%
See 3 more Smart Citations